Assessing the Performance of Thin-Film Nanofiltration Membranes with Embedded Montmorillonites - Micah Belle Marie Yap Ang; Amira Beatriz Gaces Deang; Ruth R. Aquino; Blessie A. Basilia; Shu-Hsien Huang; Kueir-Rarn Lee; Juin-Yih Lai (Membranes, 2020)
In this study, the basal spacing of montmorillonite (MMT) was modified through ion exchange. Two kinds of MMT were used: sodium-modified MMT (Na-MMT) and organo-modified MMT (O-MMT). These two particles were incorporated separately into the thin-film nanocomposite polyamide membrane through the interfacial polymerization of piperazine and trimesoyl chloride in n-hexane. The membrane with O-MMT (TFNO-MMT) has a more hydrophilic surface compared to that of membrane with Na-MMT (TFNNa-MMT). When various types of MMT were dispersed in the n-hexane solution with trimesoyl chloride (TMC), O-MMT was well-dispersed than Na-MMT. The poor dispersion of Na-MMT in n-hexane led to the aggregation of Na-MMT on the surface of TFNNa-MMT. TFNO-MMT displayed a uniform distribution of O-MMT on the surface, because O-MMT was well-dispersed in n-hexane. In comparison with the pristine and TFNNa-MMT membranes, TFNO-MMT delivered the highest pure water flux of 53.15 ± 3.30 L∙m−2∙h−1 at 6 bar, while its salt rejection for divalent ions remained at 95%–99%. Furthermore, it had stable performance in wide operating condition, and it exhibited a magnificent antifouling property. Therefore, a suitable type of MMT could lead to high separation efficiency.